Comprehensive therapy in united airway disease: Evidence Based Case Report - Irawati, Nina; Vania, Elizabeth; Poerbonegoro, Niken Lestari; Anatriera, Raden Ayu (PERHATI-KL, 2022)
ABSTRACTBackground: The concept of the united airway disease (UAD) recognises the association between allergic inflammation in the upper and lower airways. Patients with asthma and concomitant allergic rhinitis experience more asthma-related primary and secondary care visits. Purpose: To determine the best treatment option in the case of patients with asthma related allergic rhinitis, both in the control of nasal and pulmonary symptoms. Case report: A case case of 45 years old woman with asthma related to allergic rhinitis treated with combination of intranasal steroid and asthma therapy. Clinical question: In adult patient with allergic rhinitis related to asthma, does the combination of intranasal and inhaled steroids give better clinical improvement subjectively and objectively compared to monotherapy? Method: Literature search through two different databases (PubMed and Cochrane Library) and by searching the bibliography of articles to evaluate the outcome of combination therapy and monotherapy for the disease. Result: Two articles were found relevant with the topic fulfilled the requirements and relevant with the formulation or clinical question. Conclusion: Treating the inflammation associated with allergic rhinitis may have a true impact on the control of asthma, while the failure to treat rhinitis may impair asthma control.ABSTRAKLatar belakang: Konsep United Airway Disease (UAD) mengenali adanya hubungan antara inflamasi alergi pada saluran napas atas dan bawah. Pasien asma yang bersamaan dengan rinitis alergi melakukan lebih banyak kunjungan ke perawatan primer dan sekunder terkait asma. Tujuan: Menentukan pilihan pengobatan terbaik pada pasien dengan rinitis alergi terkait asma, baik dalam pengendalian keluhan hidung maupun paru. Laporan kasus: Satu kasus seorang wanita berusia 45 tahun dengan asma yang berhubungan dengan rinitis alergi. Metode: Mengumpulkan jurnal terkait dari dua database yang berbeda (PubMed dan Cochrane Library). Pencarian artikel juga dilakukan dengan mencari pada daftar pustaka artikel untuk mengevaluasi luaran dari terapi kombinasi dan terapi tunggal untuk penyakit ini. Pertanyaan klinis: Apakah terapi kombinasi dengan steroid intranasal dan steroid hirup dapat memberikan perbaikan lebih signifikan secara subjektif maupun objektif dibandingkan dengan terapi tunggal pada pasien dewasa dengan rinitis alergi dan asma? Hasil: Didapatkan dua artikel yang relevan dengan topik, sesuai dengan pertanyaan klinis serta memiliki penilaian kritis yang baik. Kesimpulan: Mengobati peradangan yang terkait dengan rinitis alergi dapat berdampak nyata pada pengendalian asma, sedangkan kegagalan untuk mengobati rinitis dapat mengganggu pengendalian asma.